African languages from a Role and Reference Grammar perspective Studies on the syntax-semantics-pragmatics interface - Fleischhauer, Jens; Kihara, Claudius Patrick (De Gruyter, 2023)
African languages cover more than one fourth of the world's languages, but still have been underrepresented in linguistic theories. The volume intends to fill this gap and addresses aspects of the syntax-semantics-pragmatics interface of African languages from a Role & Reference Grammar perspective. Accordingly, distinctive linguistic phenomena of iziZulu, Gĩkũyũ, Igbo, Babungo, Emai and other African languages are discussed in the contributions.